Visite pastorali e dinamiche comunitarie. La Valle Varaita saluzzese nella prima età moderna - Corniolo, Elena (Rivista di storia della Chiesa in Italia, 2024)
The article focuses on community relations described and also generated by the practice of the pastoral visitation. The research analyzes four records of pastoral visitation dated between 1533 and 1584 and carried out by the bishop of Saluzzo in the Varaita Valley (Piedmont). It deals with the link between the parish and the community through lexical analysis and observation of the ceremonial and ritual practices. At that time, both institutions were structured and defined from a community perspective, they were interconnected, but separated. The long-term approach, from the late Middle Ages until the first decades after the Council of Trent, allows us to reflect on this topic, highlighting the developments.